The Science of Darkness - O'Dell, Kathryn (NewYork Cambridge University, 2014)
Come explore the dark side! Every day, we find ourselves in the dark - exploring the universe, the animal kingdom, and even ourselves. This reader examines how human and animal life depends on darkness.
Cambridge Discovery Education Interactive Readers are the next generation of graded readers - captivating topics, high-impact video, and interactive exercises designed to motivate and engage.
Glossary, Contents.
Keywords: English language; Sciences; Pre-Intermediate Level